The habenula as a novel link between the homeostatic and hedonic pathways in cancer‐associated weight loss: a pilot study. Issue 3 (25th March 2018) - Maldonado, Maria; Molfese, David L.; Viswanath, Humsini; Curtis, Kaylah; Jones, Ashley; Hayes, Teresa G.; Marcelli, Marco; Mediwala, Sanjay; Baldwin, Philip; Garcia, Jose M.; Salas, Ramiro
Abstract: Background: Little is known about the brain mechanisms underlying cancer‐associated weight loss (C‐WL) in humans despite this condition negatively affecting their quality of life and survival. We tested the hypothesis that patients with C‐WL have abnormal connectivity in homeostatic and hedonic brain pathways together with altered brain activity during food reward. Methods: In 12 patients with cancer and 12 healthy controls, resting‐state functional connectivity (RSFC, resting brain activity observed through changes inblood flow in the brain which creates ablood oxygen level‐dependent signal that can be measured usingfunctional magnetic resonance imaging ) was used to compare three brain regions hypothesized to play a role in C‐WL: the hypothalamus (homeostatic), the nucleus accumbens (hedonic), and the habenula (an important regulator of reward). In addition, the brain reward response to juice was studied. Participants included 12 patients with histological diagnosis of incurable cancer (solid tumours), a European Cooperative Oncology Group performance status of 0–2, and a ≥5% involuntary body weight loss from pre‐illness over the previous 6 months and 12 non‐cancer controls matched for age, sex, and race. RSFC between the hypothalamus, nucleus accumbens, and habenula and brain striatum activity as measured by functional MRI during juice reward delivery events were the main outcome measures. Results: After adjusting for BMI and compared with matched controls, patients with C‐WL were found to have reduced RSFC between the habenula and hypothalamus ( P = 0.04) and between the habenula and nucleus accumbens ( P = 0.014). Patients with C‐WL also had reduced juice reward responses in the striatum compared with controls. Conclusions: In patients with C‐WL, reduced connectivity between both homeostatic and hedonic brain regions and the habenula and reduced juice reward were observed. Further research is needed to establish the relevance of the habenula and striatum in C‐WL.